Transforming Spiritual Experiences into Poetry: The Role of Religious Tourism in Creative Writing Pedagogy - Diana Dzurriyatur Roviat; Anas Ahmadi; Fithriyah Inda Nur Abida (DE FACTO : Journal Of International Multidisciplinary Science, 2026)
Creative poetry writing requires linguistic competence and meaningful experiences that stimulate imagination and idea generation. This study describes the implementation of a creative poetry-writing strategy using a religious tourism model and explores students’ experiences. Employing a qualitative descriptive approach, the study involved students enrolled in a Creative Literature course at Universitas Negeri Surabaya. Data were collected through observation, interviews, and documentation of students’ poems, then analyzed using the interactive model of Miles, Huberman, and Saldaña. Findings show that religious tourism helps students generate ideas, expand imagination, and produce more meaningful poetic expressions. Visits to religious sites provided spiritual, emotional, and cultural inspiration, while also increasing motivation, creativity, and confidence. Although difficulties in diction and poetic expression remained, religious tourism proved to be an innovative experiential strategy for creative writing instruction and contributed to contextual, experience-based literary learning in higher education.